2021
DOI: 10.1002/cl2.1173
|View full text |Cite
|
Sign up to set email alerts
|

Public sector reforms and their impact on the level of corruption: A systematic review

Abstract: Background: In spite of the large number of anti-corruption reforms implemented in different countries, there has been little research that empirically and systematically assesses the impact of these efforts. Objectives:The main objective of this review is to identify what works in curbing corruption in the public sector, by meta-analyzing the findings of published and unpublished evaluations of different types of anti-corruption interventions in different countries. The focus of this review is administrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 137 publications
(300 reference statements)
0
5
0
1
Order By: Relevance
“…A Campbell Review of anti-corruption interventions also found that combinations of control and deterrence measures were the most effective approaches (Mugellini et al, 2021). The evidence in that review and in Borges et al would also appear to offer support for the potential effectiveness of an oversight model such as the Police Inspectorate in England and Wales, in which regular and thematic audits and inspections are conducted and published.…”
Section: Complaint Investigations Corruption Prevention and Independe...mentioning
confidence: 92%
“…A Campbell Review of anti-corruption interventions also found that combinations of control and deterrence measures were the most effective approaches (Mugellini et al, 2021). The evidence in that review and in Borges et al would also appear to offer support for the potential effectiveness of an oversight model such as the Police Inspectorate in England and Wales, in which regular and thematic audits and inspections are conducted and published.…”
Section: Complaint Investigations Corruption Prevention and Independe...mentioning
confidence: 92%
“…Transparency is essential to ensure compliance with legal procurement procedures, promote competition and allow for the control of bias in the contract awarding. Anessi-Pessina et al ( 2020 ) and Mugellini et al ( 2021 ) argue that a new framework is needed to effectively address corruption and abuses even more during emergencies. In this sense, citizen participation is crucial to ensure good governance, but also the deployment of mechanisms such as effective audits, accountability, and transparency.…”
Section: The Theoretical Framework: Public Procurement Corruption Ris...mentioning
confidence: 99%
“…Aktivisme sosial dapat menjadi kolaborator dalam demokrasi deliberatif saat pandemi. Bahkan, sebuah meta-analisis dari studi-studi eksperimental di negara berpendapatan rendah, menengah, dan tinggi menemukan bahwa pengawasan dari gerakan masyarakat dapat mengurangi tindakan korupsi (Mugellini et al, 2021).…”
Section: Deliberasi Untuk Demokrasi Pasca Pandemi DI Indonesiaunclassified